Biobased Vitrimeric Epoxy Networks - Marco Sangermano; Matteo Bergoglio; Sandra Schögl (Macromolecular Materials and Engineering)
Abstract The scientific strategies reported in the literature for developing biobased epoxy vitrimers are summarized. Biomass resources such as lignin, cellulose, or different vegetable oils can be exploited as biobased building blocks for epoxy thermosets as an alternative to the bisphenol‐A‐based ones. Biorenewable resources have been synthesized introducing dynamic covalent bonds in the cross‐linked networks. This combination allows to achieve cross‐linked biobased epoxy networks with thermoset‐like properties at a temperature of use, but showing (re)processability, recyclability, and self‐healing properties above a well‐defined temperature named topology freezing transition temperature (Tv).